Screening of Lipid Composition for Scalable Fabrication of Solvent-Free Lipid Microarrays - Ghazanfari, Lida; Lenhert, Steven (Frontiers in Materials, 2016)
Liquid microdroplet arrays on surfaces are a promising approach to the miniaturization of laboratory processes such as high throughput screening. The fluid nature of these droplets poses unique challenges and opportunities in their fabrication and application, particularly for the scalable integration of multiple materials over large areas and immersion into cell culture solution. Here we use pin spotting and nanointaglio printing to screen a library of lipids and their mixtures for their compatibility with these fabrication processes, as well as stability upon immersion into aqueous solution. More than 200 combinations of natural and synthetic oils composed of fatty acids, triglycerides, and hydrocarbons were tested for their pin-spotting and nanointaglio print quality and their ability to contain the fluorescent compound TRITC upon immersion in water. A combination of castor oil and hexanoic acid at the ratio of 1:1 (w/w) was found optimal for producing reproducible patterns that are stable upon immersion into water. This method is capable of large scale nano-materials integration.